ADVANCED ILLNESS AND THE AGING NETWORK. (8th November 2019) - MacPherson, Andrew
Abstract: This session will provide insights on the many ways that the aging network and the Older Americans Act is able to assist individuals, and their families, who are dealing with a serious or advanced illness.